A Slurry-Pot Abrasive Wear Test Device for Several Composite Materials - Muhandes, Hasan; Kalácska, Gábor (International Journal of Engineering and Management Sciences, 2019)
To choose the proper material for agricultural machinery we tested several materials with abrasive cloth on the pin-on-plate test device. After having the pre-results, we launched more complex abrasive testing (slurry-pot) simulating more realistic mode with soils to investigate the abrasive wear mechanism and resistance of the selected up-to-date polymeric structural materials. for this, we developed a modified slurry-pot test machine that ensures the comparability of the materials over a wide range of conditions. Through this device, several parameters could be controlled like speed, the soil particle’s hit angle on the tested surface.